The impact of planned budget deficit on stock market returns in Zimbabwe (2009-2016) - Dambaza, James (Midlands State University, 2018)
The notion that chronic budget deficits impose costs on the stock market performance through depriving the private investors of the much-needed foreign currency and rising short and long-term interest rates, has been generally recognized by experts in finance and the popular financial media. In Zimbabwe over the years, the local stock market has not been providing capital up to sustainable levels that promote business, economic growth, development, improve standards of living and most importantly ease the persistent high cost of doing business in Zimbabwe amid the persistent government budget deficit problem that plays a significant role in crowding out the private investors and companies of the much needed capital to finance their operations and this often diminishes the stock market returns. This motivated an investigation on the potential impact of planned budget deficit on stock market performance, with the aim of coming up with policy recommendations that will revive the stock market performance, help ease the budget deficit problem and boost economic performance. Using monthly time series data stretching from 2009 to 2016 and OLS regression, the study examined the impact of government budget deficit on stock returns with a model that included other macroeconomic factors which influence stock returns such as money supply, consumer price index and real interest rates. Diagnostic tests such as normality, heteroskedasticity, multicollinearity and model specification were run before model estimation. The research findings revealed that the government budget deficit has a positive significant impact on stock returns and also indicated that consumer price index is an influencing factor in determining stock returns performance. More so, the study results showed positive coefficient signs on all variables included in the model and a total of 2 out of four were statistically significant namely budget deficit and consumer price index. The study recommended the need to formulate policies and strategies that are aimed at enhancing industrialisation, enforcing developmental expenditures by government and supporting the private sector and the shadow economy through financial infrastructure development that reduce the cost of doing business. This is aimed at stimulating companies’ performance and strengthen the government’s tax systems collection to ease the budget deficit problem since it contributes to the well-being of the economy.